COMPARATIVE EFFICACY OF FERROUS SULPHATE MONOTHERAPY VERSUS COMBINATION THERAPY WITH VITAMIN C IN PEDIATRIC IRON DEFICIENCY ANEMIA: A RANDOMIZED CONTROLLED TRIAL - NAZ, H; ZAFAR, Q; JAFFAR, M; KHAN, KAA; IBRAHIM, M; BATOOL, S (Biological and Clinical Sciences Research Journal, 2024)
Iron deficiency is the single most common cause of anaemia worldwide. Treatment consists of improved nutrition and oral, intramuscular, or intravenous iron administration. Objective: To compare the outcome of monotherapy with ferrous sulphate and combination therapy with ferrous sulphate and vitamin C in children with iron deficiency anaemia. Methods: This randomised controlled trial was conducted in the Department of Pediatric Medicine, The Children's Hospital and The Institute of Child Health (CH&ICH), Multan, over six months from January 20, 2022, to July 20, 2023. A total of 166 children with iron deficiency anaemia were included in the study. Participants were randomly assigned to two groups: Group A received ferrous sulphate 5 mg/kg/day Fe²⁺ orally on an empty stomach plus vitamin C 6.3 mg/kg/day, while Group B received ferrous sulphate without additional vitamin C. Baseline and post-treatment measurements of haemoglobin, serum ferritin, and mean corpuscular volume (MCV) were taken. Data were analysed using SPSS-20, applying descriptive statistics and Student’s t-test for comparison, with a significance level set at p≤0.05. Results: Of the 166 children, 111 (66.9%) were male, and 55 (33.1%) were female. The mean age was 24.55 ± 16.23 months. Rural residents accounted for 67 (40.4%), and urban residents were 99 (59.6%). Socioeconomically, 100 (60.2%) were from poor backgrounds, and 66 (39.8%) were middle-income. Among the mothers, 81 (48.8%) were illiterate, and 85 (51.2%) were literate. Post-treatment mean haemoglobin levels increased from 11.95 ± 1.02 g/dL to 12.74 ± 0.83 g/dL, serum ferritin levels from 30.73 ± 4.29 ng/mL to 32.87 ± 4.80 ng/mL, and MCV from 70.36 ± 3.81 fL to 74.49 ± 3.59 fL. Conclusion: Combination therapy with ferrous sulphate and vitamin C in pediatric patients with iron deficiency anaemia is well-tolerated and results in significant clinical improvement with minimal adverse reactions. This approach should be considered to enhance clinical outcomes, reduce morbidity, improve quality of life, and decrease healthcare costs.